Community-Centred Issue: Socio Economic Microarchitecture in Water Village Settlement at Gaya Island, Sabah - Efenday, Muhammad Adham Nor; Ibrahim, Rahinah; Zairul, Mohd (MAJ - Malaysia Architectural Journal, 2022)
The Malaysia twelfth plan, game-changer vii theme is multiplying growth of less developed states, especially Sabah and Sarawak, to reduce the development gap. An increasing unemployment rate is especially concerning for Sabah. According to Department of Statistics, Malaysia poverty rate in Sabah about 19.5% (2019) 26.3% (2020). Livelihood assets have been widely recognized in the recent development literature to have positive consequences on poverty eradication. Therefore, job opportunities in water settlements in Gaya Island are still worrying. Some parties in the Kota Kinabalu city area and outside among the residents in water settlement because of undocumented residents in Pulau Gaya. Based on literature review and site investigation, the number of people documented on Gaya Island is about 80%. Hence, this study needs to identify the small scale or cottage industries appropriate for the people of Gaya Island to generate income. This ethnographic will study is based on two objectives (i) What are the job opportunities that could be proposed; and (ii) How develop methods to manipulate the existing spaces. This research will formulate, (i) The best spatial configuration to micro economy on water settlement and (ii) Small scale industry that could contribute to income generation. The benefits of this research will help the government agency reduce the number of poverties in Malaysia.Future research will conduct qualitative study to look in-depth on the new strategy in order generate income in water settlement.